OPTIMALISASI LAYANAN APLIKASI MUAMALAT DIN (DIGITAL ISLAMIC NETWORK) UNTUK MENINGKATKAN LOYALITAS NASABAH DI BANK MUAMALAT KANTOR CABANG PEMBANTU MADIUN - Mahmudah, Dwiyana Farizka; Linawati, Linawati; Rois, Fatqu (ITB AAS Indonesia Surakarta, 2024)
This research was conducted against the background of the rapid growth of digital advances in banking institutions. Therefore, Muamalat bank KCP Madiun must always optimize services by following the latest updates regarding the digitization of services according to customer needs. The convenience provided in the Muamalat DIN (Digital Islamic Network) application service is expected to increase the loyalty of Muamalat bank KCP Madiun customers. This research uses qualitative methods. The data sources used in this research are primary data from interviews, observations, documentation and secondary data from books, journals and supporting references. The results of this study, optimization of Muamalat DIN application services affect the increase in customer loyalty at bank Muamalat KCP Madiun. Keywords: Muamalat DIN, loyalty and optimization of the service system